2021
DOI: 10.21203/rs.3.rs-456578/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Effects of rTMS and tDCS on neuropathic pain after brachial plexus injury: A randomized placebo-controlled pilot study

Abstract: Neuropathic pain (NP) after brachial plexus injury (NPBPI) is a highly disabling clinical condition and is increasingly prevalent due to increased motorcycle accidents. Currently, no randomized controlled trials have evaluated the effectiveness of non-invasive brain stimulation techniques such as Repetitive Transcranial Magnetic Stimulation (rTMS) and Transcranial Direct-Current Stimulation (tDCS) in patients suffering from NPBPI. In this study, we directly compare the efficacy of 10-Hz rTMS and anodal 2 mA tD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 50 publications
0
1
0
Order By: Relevance
“…These results demonstrated that PSD-95 in the ACC contributes to NP by interdependent activation of NR2B.Neuropathic pain (NP), resulting from lesions or diseases of the somatosensory system, is characterized by aberrant spontaneous pain, allodynia, and hyperalgesia 1,2 . Because of the obscure mechanisms underlying NP, current therapeutic measures are often ineffective 3,4 . Studies have suggested that central and peripheral sensitization are the fundamental factors involved in NP [5][6][7] .…”
mentioning
confidence: 99%
“…These results demonstrated that PSD-95 in the ACC contributes to NP by interdependent activation of NR2B.Neuropathic pain (NP), resulting from lesions or diseases of the somatosensory system, is characterized by aberrant spontaneous pain, allodynia, and hyperalgesia 1,2 . Because of the obscure mechanisms underlying NP, current therapeutic measures are often ineffective 3,4 . Studies have suggested that central and peripheral sensitization are the fundamental factors involved in NP [5][6][7] .…”
mentioning
confidence: 99%